Desenvolvimento de sistema para obtenção de filmes finos supercondutores de alta temperatura crítica (HTS) por deposição por laser pulsado (PLD) - Cichetto Júnior, Leonélio (2013)
In this PhD work, the building of a PLD (Pulse Laser Deposition) system was accomplished with resources provided by FAPESP / CEPID / CMDMC, for the purpose of depositing thin films using an 248 nm pulsed excimer laser as external power source. The project presented here demonstrates that this work has the distinction of being a pioneer in Brazil in which says respect to superconducting thin film deposition trough PLD technique. Deposition of YBCO (YBa2Cu3O7-δ) thin films was the process chosen by us to calibrate and test the assembled system, as well as to learn the details of superconducting thin films deposition. The context of this work consists in a historical introduction to the laser deposition technique, comparison of techniques for thin film deposition trough physical methods and a brief review of the superconductivity theory and the theory of thin film growth. In the experimental part, we describe the assembly of the PLD system in detail, as well as we describe the analysis of the principal parameters that say respect to the technique and the fabrication of the targets utilized in the deposition. Finally, we describe the results of the characterization techniques applied to the study of thin films deposited by PLD. X ray diffraction(XRD), scanning electron microscopy (SEM) and DC magnetic susceptibility measurements were used to analyze the superconducting thin films. Due to it pioneer condition, this work enables the Group of Materials and Devices (GMD - DF / UFSCar) as well as the CMDMC to engage in new research, not only in superconducting materials, but also in the fabrication of devices based on thin films, such as sensors, multi-components heterostructures, RAM memories, electrodes, polymers, biocompatible thin films, the GMR effect, graphene, among others, that can be fabricated precisely and controllably by the PLD technique.